(untitled) (International Journal of Food and Nutritional Sciences, 2024)
In this modern world we know that there are a lot of news websites and they cover news on various topics, out of which very few are of our interest. A new aggregator can be a tool to save a lot of time and with some modifications and filtrations we can fine tune it to show only news of our interest. A news aggregator is a very useful application to view information within minimum time. We can build a news aggregator application by scrapping some famous websites and serving the scrapped articles via Django on web or in any app. It is a web application which aggregates data from multiple websites. Then shows the articles on desired pages.News is a very important start of the day. There are well known news sites online. Now, imagine opening several news websites every single day. The time wasted from reading from those websites and information gaining is also essential. It can give leverage over those who don’t have it. Now, we have made this task really easy for everyone!! In a news aggregator, you can read news from various websites. Then the news aggregator collects the article for you. And just after a click or two, you can view news of your choice.